Characterization of the Wood Mycobiome of Vitis vinifera in a Vineyard Affected by Esca. Spatial Distribution of Fungal Communities and Their Putative Relation With Leaf Symptoms - Del Frari, Giovanni; Gobbi, Alex; Aggerbeck, Marie Rønne; Oliveira, Helena; Hansen, Lars Hestbjerg; Ferreira, Ricardo Boavida (Frontiers in Plant Science, 2019)
Esca is a disease complex belonging to the grapevine trunk diseases cluster. It comprises five syndromes, three main fungal pathogenic agents and several symptoms, both internal (e.g. affecting the stem) and external (i.e. affecting leaves and bunches). The etiology and epidemiology of this disease complex remain, in part, unclear. Some of the points that are still under discussion concern the sudden rise in disease incidence, the simultaneous presence of multiple wood pathogens in affected grapevines, the causal agents and the discontinuity in time of foliar symptoms manifestation. The standard approach to the study of esca has been mostly through culture-dependent studies, yet, leaving many questions unanswered. In this study, we used Illumina® next-generation amplicon sequencing to investigate the mycobiome of the wood of grapevines in a vineyard with history of esca. We characterized the wood mycobiome composition, investigated the spatial dynamics of the fungal communities in different areas of the stem and in the canes, and assessed the putative link between mycobiome and foliar symptoms. An unprecedented diversity of fungi is presented (289 taxa), including five genera reported for the first time in association with grapevine’s wood (Debaryomyces, Trematosphaeria, Biatriospora, Lopadostoma and Malassezia) and numerous hitherto unreported species. Esca-associated fungi Phaeomoniella chlamydospora and Fomitiporia sp. dominate the fungal community, and numerous other fungi associated with wood syndromes are also encountered (e.g. Eutypa spp., Inonotus hispidus). The spatial analysis revealed different abundances of taxa, the exclusive presence of certain fungi in specific areas of the plants, and tissue specificity. Lastly, the mycobiome composition of the woody tissues in proximity to the canopy that manifested foliar symptoms of esca, as well as in foliar symptomatic canes, was highly similar to that of plants not exhibiting any foliar symptomatology. This observation supports the current understanding that foliar symptoms are not directly linked with the fungal community in the wood. This work builds to the understanding of the microbial ecology of the grapevines wood, offering insights and a critical view on the current knowledge of the etiology of esca.